2015
DOI: 10.1177/1937586715619740
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Cues in Double-Occupancy Rooms to Support Patients With Dementia

Abstract: As this study indicated, the environmental cues color and number are helpful for these patients to identify their bed and wardrobe. However, these cues were most effective from the third to the fifth day after admission. To sustain their effectiveness on patients' identification abilities during their hospital stay, we discuss, whether verbal prompting and an ongoing mentioning of such cues, embedded in the daily work of nurses, could be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…In their review of the literature about the use of color in designing spaces for persons with dementia, Tofle, Schwarz, Yoon, and Max-Royale (2004) stated, “the evidence-based knowledge, however, for making informed decisions regarding color application has been fragmented, sporadic, conflicting, anecdotal, and loosely tested” (p. 4). In one small non-randomized study, people with dementia found hospital rooms enhanced with bright color (either red or green) more effectively than non-enhanced rooms; however, the effect was short-lived (Motzek, Bueter, & Marquardt, 2016). Another study found that color was identified by persons with dementia as being important for learning how to find their rooms in a newly redesigned dementia unit (Gibson, MacLean, Borrie, & Geiger, 2004).…”
Section: Salient Cuesmentioning
confidence: 99%
“…In their review of the literature about the use of color in designing spaces for persons with dementia, Tofle, Schwarz, Yoon, and Max-Royale (2004) stated, “the evidence-based knowledge, however, for making informed decisions regarding color application has been fragmented, sporadic, conflicting, anecdotal, and loosely tested” (p. 4). In one small non-randomized study, people with dementia found hospital rooms enhanced with bright color (either red or green) more effectively than non-enhanced rooms; however, the effect was short-lived (Motzek, Bueter, & Marquardt, 2016). Another study found that color was identified by persons with dementia as being important for learning how to find their rooms in a newly redesigned dementia unit (Gibson, MacLean, Borrie, & Geiger, 2004).…”
Section: Salient Cuesmentioning
confidence: 99%
“…As mentioned previously, signs of names and assigned numbers with selfreferent items helped improve PwD's room recognition (Nolan et al, 2001). Signages with contrasting colors and information were also helpful for PwD's navigation (Eastham & Cox, 2017;Motzek et al, 2016). Bracken-Scally et al…”
Section: Resultsmentioning
confidence: 91%
“…As mentioned previously, signs of names and assigned numbers with self-referent items helped improve PwD’s room recognition (Nolan et al, 2001). Signages with contrasting colors and information were also helpful for PwD’s navigation (Eastham & Cox, 2017; Motzek et al, 2016). Bracken-Scally et al (2019) reported that a functional electronic display in the emergency department was believed as a helpful orientation aid for PwD by family caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, simple environmental changes, such as door camouflage and environmental cues may, at least initially improve door testing and wayfinding. ( 11 , 12 )…”
Section: Discussionmentioning
confidence: 99%
“…Motzek et al . ( 12 ) studied the effectiveness of environmental cues on patients’ abilities to identify their beds and wardrobes on an acute geriatric ward (N = 42). They labeled patients’ beds and wardrobes with the environmental cues “colour” and “number”.…”
Section: Interventions Typesmentioning
confidence: 99%